Odpowiedź :
Witaj :)
[tex]\frac{(1+\sqrt{12})^2-(2\sqrt{3})(\sqrt{3}-2)}{(\sqrt{8}-2)(2+2\sqrt{2})} =\frac{(1+\sqrt{4\cdot3})^2-2\sqrt{9}+4\sqrt{3}}{(\sqrt{4\cdot2}-2)(2+2\sqrt{2})}= \frac{(1+2\sqrt{3})^2-6+4\sqrt{3}}{(2\sqrt{2}-2)(2+2\sqrt{2})} =\\\\=\frac{1^2+2\cdot1\cdot2\sqrt{3}+(2\sqrt{3})^2-6+4\sqrt{3}}{(2\sqrt{2})^2-2^2} =\frac{1+4\sqrt{3}+12-6+4\sqrt{3}}{8-4} =\frac{7+8\sqrt{3}}{4}[/tex]
Zastosowano następujące wzory skróconego mnożenia:
[tex](a+b)^2=a^2+2ab+b^2\\\\(a-b)(a+b)=a^2-b^2[/tex]